SHARING KNOWLEDGE AND INSPIRATION: A LEARNING PROGRAM AT THE AR-RAHMAN ORPHANAGE IN PALOPO AS A FORM OF COMMUNITY SERVICE: BERBAGI ILMU DAN INSPIRASI: PROGRAM PELAJARAN DI PANTI ASUHAN AR-RAHMAN PALOPO SEBAGAI BENTUK PENGABDIAN - Nurul Qisti; Putriani; Muhammad Rangga Sain; Alvianus Tandi Bunga; Rais; Ningrat; Muhammad Rifky Iskandar; Marisa Sasha Salsabila; Airin; Muhammad Mihdat Salman; Nurul Oktapia; Namira Nurul Magfira; A. Fahri A. Baco; Reni Verlina Gosa; Restya Ningsih S. Takko (PT. ROCE WISDOM ACEH, 2026)
The “Educating Together and Sharing Knowledge” program is a concrete form of community serviceimplemented through teaching activities at the Ar-Rahman orphanage in Palopo City. This activity aims to increase orphanage children's knowledge and learning motivation through an educational and inspirational approach. The program implementation method includes providing general lesson materials and games. The activity results show increased enthusiasm, active participation, and interest in learning among the children involved. Thus, this activity not only benefits orphanage children but also strengthens the values of social care, empathy, and responsibility among the activity implementers.